Homogenized and pore-scale analyses of forced convection through open cell foams. (August 2018) - Vijay, Dig; Goetze, Pitt; Wulf, Rhena; Gross, Ulrich
Highlights: A methodology is presented to design thermal transportation applications of open cell foams. A kelvin cell based simplified structure is investigated as a potential representative of open cell foams. It is found that simplified structures cannot represent actual foams due to their tortuous nature. Finally, the presented methodology is applied on the actual foam structures. Abstract: Open cell foams have desirable geometrical characteristics that make them a suitable choice in various heat exchanger applications. The objective of this study is to determine such volume-averaged key parameters that can characterize the complex thermal transportation process through open cell foams. These key parameters are represented by effective thermal conductivity, k e, volumetric heat transfer coefficient, hv, and dispersion conductivity, k d . In order to determine these parameters, detailed pore-scale simulations through the representative element volumes (REVs) of the actual foam structures are performed. Moreover, knowing the fact that the successful implementation of simplified foam structures as a suitable representative of the actual foam structures can simplify the complexity of the problem, it is also investigated. In the presented work, various microscopic pore-scale models are implemented for both simplified and actual foam structures to determine the key parameters. Subsequently, these key parameters are implemented into two different homogenized macroscopic models to predict the temperature fields of large-scale steady-state and transient forced convection processes. The numerical outcomes of homogenized macroscopic models are validated with the experimental data, which is available for a set of ceramic foams having different pore size (10–30 PPI) and porosity (79–87%). As a consequence of the validation process, the findings of this study reveal that the proposed methodology successfully predicts the values of the concerned key parameters. Further, it is observed that simplified foam structures cannot represent the actual foam structures, as the tortuous shape of open cell foams bound to enhance the advection and dissipation of heat due to recirculation and eddy formation.